THE LAW GOVERNING HUMAN EXPERIMENTATION IN QUÉBEC - Kouri, Robert (Revue de droit de l'Université de Sherbrooke, 1991)
This article is intended to provide an overview of the law governing human experimentation in Quebec as such law presently stands, and to examine certain innovations introduced by the proposed Civil Code of Québec. It examines more particulary, the conditions under which human experimentation may take place and the liability of the parties involved in research.